Final Qualification Paper in University in the Context of Artificial Intelligence Proliferation: University Students’ Perspective - N. V. Tikhonova; N. P. Pomortseva (Высшее образование в России)
Final qualifying paper is the important part of university studies, demonstrating the quality of students’ mastering of the educational program. However, in the context of the spread of artificial intelligence (AI), the question arises about the objectivity and appropriateness of using this form of assessment. In order to make informed decisions in this area, it is necessary to analyze the opinion of the main educational stakeholders. Despite the numerous surveys of students regarding the use of artificial intelligence in the learning process, there are practically no works aimed at identifying the practices and strategies of students’ use of AI in research activities. This article aims to fill the existing gap. The aim of the study is to identify the attitude of senior undergraduates of the Higher School of Foreign Languages and Translation Studies of Kazan Federal University to the process of writing and defending the final qualifying paper in the context of AI proliferation. The results of interpreting the survey of graduates allow the authors to determine a positive trend in the undergraduate’s interaction with the supervisor as compared to the similar surveys conducted before. An obvious challenge to the system of higher education appeared the critical attitude of students to “Antiplagiarism” system and a tendency to a positive perception of the AI role in writing a thesis (only 10,7% of respondents consider the use of AI in writing a final paper unethical). At the same time, there is a direct link between the use of AI and ethical approval of its use. However, the authors predict the improvement in the situation after the introduction of lecture and practical disciplines and research practice during the senior year of the bachelor’s degree. The assumption is based, as provided in the article, on the best practice of organizing research work of the students majoring in Linguistics. It is implemented in various forms: lecture courses, practical classes, field practice, final paper draft defense as well as mock defense of the bachelor’s qualifying paper. The authors come to the conclusion that an increase in the quality of training a university graduate is possible with the implementation of a comprehensive differentiated approach to the organization of research work combined with effective tackling of ethical problems of scientific activity of a university student.